COMMUNITY EMPOWERMENT IN EFFORTS TO IMPROVE DENTAL AND ORAL HEALTH THROUGH TRAINING OF TRAINER ACTIVITIES IN “ANAK BANGSA ELEMENTARY SCHOOL” SURABAYA - Widowati, Kharinna; Indarti, Caecilia; Sari, Rima Parwati; Prananingrum, Widyasri; Hollanda, Ghita Hadi; Emilda, Yulie; Parasihni, Kristanti; Karsini, Isidora; Elidasari, Monica; Agustia, Lita; Santoso, Budi; Lestari, IGAM Oka; Rizka, Yoifah; Hadinata, Yongki; Rochyani, Linda (LPPM Univ. Ibn Khaldun Bogor, 2024)
One way to develop health is community empowerment in the field of dental and oral health. Based on the 2018 Basic Health Research, it was reported that the prevalence of dental and oral problems in Indonesia is still very high. As many as 93% of school-aged children experience dental and oral problems. This is due to a lack of knowledge and lack of awareness of the Indonesian population regarding dental hygiene. In a series of activities for the 2023 National Dental Health Month, dental and oral health education programs are carried out in schools/School Health Programs. Method: The method is carried out using a cadre training program / Training of Trainers through zoom meetings for teachers and parents of students by providing dental and oral health material. Next, ask them to provide assistance with morning and evening toothbrushing activities for 21 days, teaching children about the benefits of good oral hygiene and showing them how to brush their teeth twice a day. It is preceded by a pretest and at the end of the delivery of the material a post test is given. The results of the evaluation of understanding of the material presented show that there is a significant difference in the pre-test and post-test of prospective cadres, which means that the cadres understand the material well. The new habit of brushing teeth has been quite successful from the uploaded photo documentation and students have recorded well for 21 days. This shows a change in behavior in maintaining dental and oral health.